2009
DOI: 10.1212/wnl.0b013e3181c51a7d
|View full text |Cite
|
Sign up to set email alerts
|

Stroke literacy in Central Harlem

Abstract: Background: Awareness of stroke warning symptoms and risk factors (stroke literacy), as well as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 19 publications
4
69
0
Order By: Relevance
“…Though the stroke literacy study by Willey et al found no significant difference in symptoms recognition between African Americans and Whites, recognition of blurred vision and headache was poor for both groups. 7 However, in our Baltimore-based study, 77.5% of participants identified "all of the above" (weakness, slurred speech, and vision loss) as the correct answer to a multiple choice question regarding stroke symptoms.…”
Section: Signs and Symptomsmentioning
confidence: 68%
See 3 more Smart Citations
“…Though the stroke literacy study by Willey et al found no significant difference in symptoms recognition between African Americans and Whites, recognition of blurred vision and headache was poor for both groups. 7 However, in our Baltimore-based study, 77.5% of participants identified "all of the above" (weakness, slurred speech, and vision loss) as the correct answer to a multiple choice question regarding stroke symptoms.…”
Section: Signs and Symptomsmentioning
confidence: 68%
“…Willey et al reported on a stroke literacy survey in Central Harlem in which 56.3% of African Americans compared with 72.7% of Whites correctly identified the brain in a multiple choice question. 7 Biederman et al reported on a telephone survey of two counties in North Carolina in which 59.6% of African Americans compared with 77.7% Whites answered correctly to an open-ended question that stroke occurs in the brain or head. 12 Similarly, 50.7% of participants in a telephone-based survey of African Americans in Detroit responded that a stroke occurs in the brain.…”
Section: Location Of Strokementioning
confidence: 99%
See 2 more Smart Citations
“…Among individuals who survive a stroke, hemiparesis or hemiplegia is the most frequent m o t o r d e f i c i e n c y, w i t h c o r r e s p o n d i n g p h y s i c a l limitations 2,3) . The important issues in rehabilitation of stroke patients include restoring activity and participation.…”
Section: Introductionmentioning
confidence: 99%